Transcriptome analyses of the ginseng root rot pathogens Cylindrocarpon destructans and Fusarium solani to identify radicicol resistance mechanisms - Li, Taiying (J Ginseng Res, 2020)
BACKGROUND: The ascomycete fungi Cylindrocarpon destructans (Cd) and Fusarium solani (Fs) cause ginseng root rot and significantly reduce the quality and yield of ginseng. Cd produces the secondary metabolite radicicol, which targets the molecular chaperone Hsp90. Fs is resistant to radicicol, whereas other fungal genera associated with ginseng disease are sensitive to it. Radicicol resistance mechanisms have not yet been elucidated. METHODS: Transcriptome analyses of Fs and Cd mycelia treated with or without radicicol were conducted using RNA-seq. All of the differentially expressed genes (DEGs) were functionally annotated using the Fusarium graminearum transcript database. In addition, deletions of two transporter genes identified by RNA-seq were created to confirm their contributions to radicicol resistance. RESULTS: Treatment with radicicol resulted in upregulation of chitin synthase and cell wall integrity genes in Fs and upregulation of nicotinamide adenine dinucleotide dehydrogenase and sugar transporter genes in Cd. Genes encoding an ATP-binding cassette transporter, an aflatoxin efflux pump, ammonium permease 1 (mep1), and nitrilase were differentially expressed in both Fs and Cd. Among these four genes, only the ABC transporter was upregulated in both Fs and Cd. The aflatoxin efflux pump and mep1 were upregulated in Cd, but downregulated in Fs, whereas nitrilase was downregulated in both Fs and Cd. CONCLUSION: The transcriptome analyses suggested radicicol resistance pathways, and deletions of the transporter genes indicated that they contribute to radicicol resistance.